2020
DOI: 10.1101/2020.09.04.20188219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex disparity in acute myeloid leukemia – evidence from a study of FLT3-ITD mutated patients

Abstract: Little attention has been directed at untangling sex-related molecular and phenotypic differences in AML. While increased incidence and poor risk is generally associated with a male phenotype, FLT3-ITD, NPM1 and DNMT3A mutations are overrepresented in female AML. Here, we have investigated the relationship between sex and FLT3-ITD mutation status by comparing clinical data, mutational profiles, gene expression and ex vivo drug sensitivity responses in four cohorts: the Beat AML cohort, the LAML-TCGA cohort and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Of note, it was recently reported that risk-adapted treatment strategies in AML appear to have eliminated the poor risk association with FLT3-ITD [72]. We have confirmed this observation in the HOVON cohorts in a separate study; FLT3-ITD mutated patients in C1 had a significantly worse outcome compared to patients with FLT3wt, while there was no difference in overall survival between FLT3wt and FLT3-ITD in C2 [73]. Interestingly, in the present study we still identified a poor risk association with high mutational burden within the FLT3-ITD mutated subgroup of this cohort.…”
Section: Discussionsupporting
confidence: 83%
“…Of note, it was recently reported that risk-adapted treatment strategies in AML appear to have eliminated the poor risk association with FLT3-ITD [72]. We have confirmed this observation in the HOVON cohorts in a separate study; FLT3-ITD mutated patients in C1 had a significantly worse outcome compared to patients with FLT3wt, while there was no difference in overall survival between FLT3wt and FLT3-ITD in C2 [73]. Interestingly, in the present study we still identified a poor risk association with high mutational burden within the FLT3-ITD mutated subgroup of this cohort.…”
Section: Discussionsupporting
confidence: 83%
“…The higher incidence of “pre-leukemic” mutations in men with AML was also highlighted by Metzeler et al who showed that mutations in RUNX1 , ASXL1 , SRSF2 , STAG2 , and BCOR genes were more prevalent in men compared to women in a cohort of 664 AML patients [ 33 ]. Finally, Engen et al reported in a preprint article that men with FLT3-ITD mutated AML have higher incidence of RUNX1 , ZRSR2 , SRSF2 , U2AF1 , ASXL1 and EZH2 mutations [ 34 ]. These results indicate a male predilection for mutations that have been reported to drive the progression of chronic myeloid neoplasms and their transformation to AML.…”
Section: Sex-related Differences In the Genomic Profile Of Patientmentioning
confidence: 99%
“…In the current study the age of patients distribution between 18-66 years, that may be related to the disease genes and some molecular features, that was most pronounced in the AML patients (Lindsley et al,2015). The age distribution by sex of leukemia patients, which is characterized by demography, indicates an important influence of age composition, and this can make age-matching the optimal condition for comparison (Engen et. al.,2020).…”
Section: Results Distribution Of Patients With Acute Myeloid Leukemiamentioning
confidence: 72%